2020
DOI: 10.3389/fmolb.2020.00001
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Binding Sites for GK Domain of DLG1 and DLG4 via Molecular Dynamics Simulation

Abstract: Discs-large (DLG) is a member that belongs to the membrane-associated guanylate kinase (MAGUK) family. The GK domain of DLGs has evolved into a protein-protein interaction module that could bind with kinds of proteins to regulate diverse cellular functions. Previous reports have demonstrated the GK domain of DLGs functioned as a phosphor-peptide-binding module by resolving the crystal structures. Here we investigated into the interactions of DLG1 and DLG4 with their reported phosphor-peptides by molecular dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…Taken together, this suggests that it exhibits the strongest and most stable binding. This result is in agreement with previously published data that suggest that rutin (docking score: − 9.16 kcal/mol) is the most potent inhibitor for 6LU7 [ 31 ] . Other researchers have also reported that rutin is an effective inhibitor of various targets of the SARS-CoV-2 proteases [ 32 ] .…”
Section: Discussionsupporting
confidence: 93%
“…Taken together, this suggests that it exhibits the strongest and most stable binding. This result is in agreement with previously published data that suggest that rutin (docking score: − 9.16 kcal/mol) is the most potent inhibitor for 6LU7 [ 31 ] . Other researchers have also reported that rutin is an effective inhibitor of various targets of the SARS-CoV-2 proteases [ 32 ] .…”
Section: Discussionsupporting
confidence: 93%
“…The Covid-19 pandemic has sparked intense research into the structure of the SARS-CoV-2 coronavirus aimed to understand its mechanism of infection and hamper its virulence [ [1] , [2] , [3] ]. The SARS-CoV-2 RNA genome encodes several membrane proteins, one of which, the envelope protein E, is a small hydrophobic protein with ion channel activity localized at the endoplasmic reticulum-Golgi intermediate compartment (ERGIC).…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 RNA genome encodes several membrane proteins, one of which, the envelope protein E, is a small hydrophobic protein with ion channel activity localized at the endoplasmic reticulum-Golgi intermediate compartment (ERGIC). Importantly, the E protein of SARS-CoV-2 shares a high degree of similarity with the severe acute respiratory syndrome coronavirus (SARS-CoV) E protein studied here and their transmembrane domains – responsible for the ion channel activity – have identical amino acid sequences [ 1 , 2 , 4 ]. In addition, recent in silico studies predict analogous ion channel activity of both proteins [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel strategies employing small interfering RNAs (siRNAs), microRNAs (miRNAs), and locked nucleic acid antisense oligonucleotides (LNA) or GapmeRs, targeting, for instance, the 5′URT or regions of the Spike molecule, represent potential therapeutic tools for both prophylaxis and therapy of COVID-19 [ 101 – 103 ]. Indeed, the design of antisense oligonucleotides, such as Miravirsen, under investigation for HCV treatment, could be used to inhibit viral replication by scavenging miRNAs that are involved in the process [ 104 , 105 ]. These studies suggest that RNA-based drugs could be optimized and employed to interfere with SARS-CoV-2 replication and transcription.…”
Section: Epigenetic Implication In Sars- Cov-2 Infection and Therapymentioning
confidence: 99%